A streamlined method for pressurized extraction and fractionation of leaf lipids. (September 2022) - Wang, Zhao; White, Joseph; Thomas, Jonathan; Hockaday, William C.
Highlights: New ASE methods proposed for cleanup and separation of leaf lipids. Leaf lipid composition/yields differ with in-cell adsorbents and solvent polarity. Yields of n -alkyls, sterols and terpenoids greater in the new methods. n -Alkanes/alcohols were separated from the corresponding acids using the methods. Abstract: Plant leaf lipids are complex mixtures, which may include n -alkanes, n -alkanols, fatty acids, phenolic compounds, phytosterols, terpenes, flavonoids, and alkaloids. Many of these compounds are also widely distributed in sediments and soils, preserving molecular and isotopic information that aids the study of past climatic and ecological variables. Sample preparation typically requires multi-step extraction and fractionation procedures, making it impractical to process large numbers of samples in most laboratories. This study reports a streamlined method of leaf lipid extraction, cleanup and fractionation on commercial pressurized solvent extraction systems. A method using solid-phase adsorbents placed within the sample cell during total lipid extraction, eliminating the need for subsequent cleanup procedures, is referred to as solid phase in-cell cleanup (SPIC). Additionally, we demonstrate the feasibility of lipid fractionation according to functional group chemistries by combining in-cell solid-phase adsorption with a serial addition of protic solvents, which we refer to as solid phase in-cell fractionation (SPIF). We applied SPIC to angiosperm leaves, Morus celtidifolia, and SPIF to gymnosperm leaves of Juniperus ashei and lacustrine sediment . Molecular yields were measured by gas chromatography–mass spectrometry and compared to traditional gravity-fed silica gel column fractionation. The SPIC yields of n -alkanes, n -alkanols, and n -alkanoic acids from M. celtidifolia leaves were greater than traditional silica gel column fractionation by 37%, 83% and 59%, respectively. SPIF was highly effective in separating hydrocarbons and alcohols from the corresponding acids. The time for using SPIC/SPIF was 1.8-fold less per sample than that involved in using traditional columns.